Traumatic Injuries Requiring Simultaneous Emergent Operative Procedures, Knife Wounds to the Top of the Skull and the Abdomen - Matthews, L Ray; Cooper, Moungar; Carney, David; Danner, Omar; Nguyen, Jonathan; Gilzenrat, Keren Bashan; Moore, Carolyn; Udobi, Kahdi; Childs, Ed; Rhee, Peter; Taha, Assad (Global Journal of Medical and Clinical Case Reports, 2017)
The simultaneous commencement of operative interventions by two or more surgical teams in the multiply injured patient is gaining more acceptance. We describe a rare case of concomitant penetrating injuries to the brain, chest and abdomen that required an orchestrated immediate approach and resulted in a good outcome. Both injuries were life threatening. A coordinated effort between Trauma Surgery and Neurosurgery working simultaneously produced an excellent outcome for this patient.